PENGARUH PNGEMBANGAN KARIR, EMPLOYEE ENGAGEMENT DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Pada The Bagong Adventure Museum Tubuh Kota Batu) - Mutiansi Hanifah; Abd Kodir Djaelani; M Ridwan Basalamah (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABTRACT                This research was conducted to find out how much influence the Career Development, Employee Engagement and Organizational Culture variables on Employee Performance. Study at The Bagong Adventure Museum Batu City Body. In this study 55 population of people using saturated sampling. The sample used was taken from The Bagong Adventure Museum Body employees. To find out the data that will be examined later, this study uses a way to distribute questionnaires to better know the opinions of employees by filling out the statements that have been attached to the questionnaire.               Also in this study using SPSS measuring tools to test data in the form of instrument testing, multiple linear regression analysis, testing classic assumptions, and testing hypotheses. From this study produced several conclusions that state that the variables of Career Development, Employee Engagement and Organizational Culture influence together so as to improve the Performance of The Bagong Adventure Museum Body Employees. While partial employee engagement does not affect employee performance, while career development and organizational culture have an influence on employee performance. Keyword: Career Development, Employee Engagement, Organizational Culture, Employee Performance.